Glycosylation studies on conformationally restricted 3,5-O-(di-tert- butylsilylene)-d-galactofuranosyl trichloroacetimidate donors for 1,2-cis α-d-galactofuranosylation - Tilve, Mariano Javier (2011)
Conformationally restricted 3,5-O-di-tert-butylsilylene-d-galactofuranosyl trichloroacetimidate donors were synthesized from allyl α-d- galactofuranoside for the construction of 1,2-cis α-d-galactofuranosyl linkages. Glycosylation reactions were performed with several acceptors, including d-galactono-1,4-lactone, d-rhamnopyranosyl, and d-mannopyranosyl derivatives. The influence of the temperature and the reaction solvents was evaluated, as well as the 6-O-substitution pattern of the donor. The higher α-selectivities were obtained at -78 °C in diethyl ether as solvent. 6-O-Acetyl substitution on constrained donor increased the α-selectivity compared to the 6-O-benzyl substitution. Almost no selectivities were observed in the non-participating solvent CH 2Cl 2. In contrast, ethereal solvents enhanced the α-selectivity suggesting a participating effect in the reaction intermediate.